Solid Electrolyte Interphase Architecture Determined through In Situ Neutron Scattering. Issue 6 (14th June 2021) - Veith, Gabriel M.; Browning, Katie L.; Doucet, Mathieu; Browning, James F.
Abstract : We demonstrate through a combination of in operando solvent exchange and depth-sensitive neutron reflectometry that the solid electrolyte interphase (SEI) formed after the initial lithiation of a silicon anode, using a standard LiPF6 ethylene carbonate/ethyl methyl carbonate electrolyte, is chemically homogeneous across the liquid-solid interface. The data show the SEI is accessible to solvent/salt exchange throughout the layer indicating the poorly bound nature of the SEI components. Further, the data indicates that P-F species, from the decomposition of the LiPF6 salt, are highly mobile and removed from the SEI with solvent exchange. Critically, the SEI layer is structurally homogenous, in contrast to the reports in the literature of an inorganic/organic bilayer, which is important to our understanding of SEI formation and chemistry.